Comparative Study on the Effects of Ceftriaxone and Monocytes on Recovery after Spinal Cord Injury in Rat - Javad Tajkey; Alireza Biglari; Bohlol Habibi Asl; Ali Ramazani; Saeideh Mazloomzadeh (Advanced Pharmaceutical Bulletin, 2015)
Purpose: Comparison between the efficacy of ceftriaxone and monocytes on improvement of neuron protection and functional recovery after spinal cord injury (SCI) in rat. Methods: Rats were randomly divided into three groups of ten. Spinal cord injury was performed on rats under general anesthesia using the weight dropping method. Ceftriaxone was injected intraperitoneally 200 mg/kg/day for seven days after SCI. Monocytes were injected 2 × 105 cells 4 days after SCI. Hind limb motor function was assessed using the Basso, Beattie and Bresnahan (BBB) scale. Corticospinal tract (CST) axons were traced by injection of biotin dextran amine (BDA) into the sensorimotor cortex. Results: There were statistically significant differences in BBB scores in ceftriaxone in comparison to both monocytes receiving and control groups. On the other hand there were statistically significant differences in axon counting in both ceftriaxone and monocytes receiving groups in comparison to control group. Conclusion: Our findings suggest that ceftriaxone improves functional recovery more effective than monocytes in rats after SCI. These results are from an experimental model and validation is required for further investigation.